Are data available to measure progress in the coverage of essential nutrition actions in South Asia? A review of demographic and health surveys in seven countries, 2005–2018 - Jangid, Manita; Neupane, Sumanta; Scott, Samuel P.; Nguyen, Phuong Hong; Kim, Sunny S.; Menon, Purnima; Torlesse, Harriet; Murira, Zivai; Heidkamp, Rebecca A. (American Society for Nutrition, 2020)
South Asian countries carry the largest burden of undernutrition globally. The World Health Organization has recommended a set of Essential Nutrition Actions (ENA) to tackle all forms of malnutrition. Limited evidence exists on the availability of data in nationally representative surveys to analyse coverage patterns and to track progress on these actions.